Characteristics of Adolescents Affected by Mass Psychogenic Illness Outbreaks in Schools in Nepal: A Case-Control Study - Sapkota, Ram P.; Brunet, Alain; Kirmayer, Laurence J. (Frontiers in Psychiatry, 2020)
Mass psychogenic illness is generally construed as a dissociative phenomenon. We sought to test if the correlates of dissociative experiences and behaviours most commonly proposed in the literature (i.e., that explain dissociation in terms of childhood trauma, cognitive and personality traits, current level of distress, or a specific propensity for dissociative experience and behaviours) could predict caseness among students affected by episodes of mass psychogenic illness occurring in schools in Nepal. We assessed 194 cases and 190 controls (N = 384) of ages 11-18 years from 12 public schools in Nepal. Cases and controls were comparable on all demographic variables, except family configuration. In bivariate comparisons, caseness was associated with childhood trauma (especially physical abuse) as well as living in nuclear families, experience of peritraumatic dissociation, a higher dissociative tendency, and higher levels of depressive and posttraumatic stress symptoms. Hypnotizability emerged as the strongest predictor of mass psychogenic illness case status among the cognitive and personality trait variables. However, in multivariable logistic regression, the proposed correlates of dissociation did not make a significant contribution in predicting caseness suggesting that correlates of dissociative experiences and behaviours currently proposed in the literature do not adequately map the phenomenon of mass psychogenic illness. Ad-hoc Classification and Regression Trees analysis showed that if an adolescent is highly hypnotizable and reports higher rates of peritraumatic dissociative experiences then there is 73% probability that the adolescent will be a case in a mass psychogenic illness episode. Studies involving other psychological factors (i.e., secondary gain, suggestibility, absorption, expectancy, modelling and behavioral mimicry), social and cultural factors as well as school- and family-related factors are needed to understand the causes and correlates of mass psychogenic illness phenomena to guide prevention and intervention.